Development of inshot-based raga learning media on cultural diversity material for grade iii elementary school students - Aditia Wiguna, Frans; Dwi Nur Wendha , Dhian; Wahyu Aji, Tridian (Universitas Nusantara PGRI Kediri, 2023)
This research is based on the lack of understanding of third grade elementary school students about cultural diversity material because teachers tend to use conventional media, in the form of pictures from textbooks or LKS only. This study aimed to develop Inshot-based RAGA learning media. This research method used research and development (R&D) with ADDIE model. The research steps include: analysis, design, development, implementation, and evaluation. Data collection techniques used in this study are descriptive analysis techniques for observation and interview data while statistical analysis was used to calculate the percentage of results from validation, practicality, and effectiveness in the form of numbers. The results of media expert validation obtained an average score of 95.6% in the very feasible category, and material experts obtain an average score of 96.75% with a very valid category, results of media practicality with a score of 92.75% in very practical category and for scores from student responses 94.5% in very decent category, then the effectiveness data seen from the results of pre-test with a score of 67% and post-test with a score of 83%. Based on the analysis of results it can be concluded that RAGA learning media based on Inshot on cultural diversity material for Civics class III SDN Musirlor 2 has succeeded in increasing student understanding and student learning outcomes.